Do migrants think differently? Evidence from East European and post-Soviet states - Ruxanda Berlinschi; Ani Harutyunyan (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2016)
This research analyzes differences in values and beliefs between individuals in European and post-Soviet states who intend to emigrate and those who do not. In particular, we investigate which political, economic and social values and beliefs are significant determinants of the intention to emigrate, after controlling for relevant socio-economic and demographic confounding factors. The results indicate that self-selection patterns exist in some dimensions, such as evaluation of home country governance and institutions, political participation and trust in other people, while they are absent in other dimensions, such as economic liberalism, views on democracy and free markets. Results also indicate that migrant self-selection patterns are heterogeneous across regions. This analysis aims to improve our understanding of the determinants of emigration, as well as of its possible consequences on the dynamics of governance and institutions.
Keywords: P30; F22; F63; F68; Z10; 330; Migration determinants; Culture; transition economies